The savings gap in Hungary - Rob́ert Ivań Gaĺ; Aŕpad́ Tor̈zsok̈ (Hungarian Demographic Research Institute, 2016)
In a simple cohort model we carry out a projection based on current per capita age profiles of labour income and consumption and combine them with Hungary's expected future age composition. We use 2012 Hungarian data. Due to a shrinking and ageing population this exercise predicts a growing gap between labour income and consumption in Hungary, which will~ have to be covered by asset-based revenues. We apply two balancing items: a windfall capital endowment in the base year, and gradual capital accumulation through higher savings. We also quantify how much the household economy, an integral but unregistered part of a modern economy, can absorb the effects of ageing. In addition, we test against a model using~ demographic data from 1995. The two decades between the mid-1990s and the mid-2010s offered a special demographic opportunity for Hungary and coincided with the botched prefunding experiment in the public pension system. We demonstrate the potential of this missed opportunity.
Keywords: N33; 300; macroeconomic consequences of demographic trends; National Transfer Accounts; unpaid household labour; pension reform; Alternde Bevölkerung; Rentenfinanzierung; Rentenreform; Ungarn